Analysis of Leadership Style and Work Motivation on Employee Job Satisfaction at the Representative Office of the Financial and Development Supervisory Agency of North Sumatra Province - Abdi Setiawan; Ikhah Malikhah; Helen Serta Suhartitin (International Journal of Management, Economic and Accounting, 2024)
This study aims to find out the analysis: (1) Leadership Style, on Job Satisfaction and (2) Work Motivation on Job Satisfaction (3) Leadership Style and Work Motivation on Job Satisfaction. This study uses a hypotheses testing approach. This approach is used to analyze each independent variable to the dependent variable partially. This type of research is a correlational study. This research is a field study. Field study is research conducted by making direct observations on the object being studied. The population in this study is 111 employees. The number of respondents was 53 employees at the Representative Office of the North Sumatra Provincial Financial and Development Supervisory Agency. The research sample was determined through Slovin. The research questionnaire was measured using the Likert scale. The data were analyzed using multiple linear regression analysis and tested by data quality test, classical assumption test, and data hypothesis test using SPSS 26 software. The results of this study show that (1) Leadership Style has a positive effect on Job Satisfaction. The value is shown by the value of Sig. 0.000 > 0.05 and the t-value is calculated 4,163 > 2,008. (2) Work Motivation has a positive effect on Job Satisfaction. This is shown by the Sig. value of 0.001 > 0.05 and the t-value of 3.521 >2.008. (3) Leadership Style and Work Motivation simultaneously have a positive effect on Job Satisfaction.